Analysis of Natural Resources of Marine and Fishery Policy on the Welfare of Marine Area Communities an Islamic Economic Perspective - Thaliya, Adinda; Setiawan, Agung Bhakti; Nandri, Annisa Ayu; Permata, Tiara Bunga; Amrina, Dania Hellin (Journal of Economics Research and Social Sciences, 2021)
This research aims to determine how marine and fisheries policies in Indonesia and the implementation of these policies on the welfare of the society in the Bandar Lampung Sea area from the perspective of Islamic economics. So later, the results of this research can be used as examples and role models for other marine areas about the implementation of good marine and fisheries policies. The research was conducted with a qualitative descriptive research method that uses a literature study that considers and continues the results of previous studies. The type of sample used in this research is purposive sampling. The sample in this research is the community around the Gudang Lelang market and through random sampling technique. This research indicates marine and fisheries policies, especially at Pasar Gudang Lelang, Ikan Bawal street, Kangkung sub-district, Bandar Lampung City. Among others, protecting the diversity of marine organisms, minimizing the exploitation of marine and fishery resources, implementing human resource development related to marine and fishery resource management, implementing capital lending as a support for businesses, and others have been implemented well. The excellent application of marine and fisheries policies can foster welfare for the community according to the main objective of Islamic economics, namely to create public order in a welfare society based on justice, equality, and balance.